Mapping the Intellectual Structure of Entrepreneurship Research: revisiting the invisible college - Montiel Campos, Hector; Solé Parellada, Francesc; Palma, Yarissa (Review of Business Management, 2012)
Along with entrepreneurship´s continuing emergence among the management sciences, there is an ongoing debate about what the field is – or should be. In this regard, to have a better understanding of the development of this research field, it is useful to understand the scientific structure. This study uses bibliometric techniques and cluster analyses to present an empirically grounded picture of the entrepreneurship research. This research analyzes the 1,112 full-length papers published in the FER Proceedings between 1981 and 2009, and the 378 articles published in the Journal of Business Venturing between 2000 and 2010. Both forums are considered representative in the exchange of entrepreneurial thought. The results indicate that entrepreneurship research published in these forums is characterized by varied themes that are not necessarily connected. Rather, they reflect the disciplinary training and lens of their authors; and considerable dynamism and change in key research themes over time. Hopefully, the results presented here provide abundant opportunities for identifying insightful, influential, and creative research topics in the entrepreneurship field. Key words: Entrepreneurship. Research. Forum. Invisible college.